THE RESPONSE OF SEVERAL TYPES OF LIQUID ORGANIC FERTILIZER (POC) TO GRASS GROWTH ODOT (Pennisetum Purpureum CV. Mott) - Roynaldi, Roynaldi; Meriksa Sembiring (Bajang Institute, 2024)
The purpose of this study was to determine the response of several types of liquid organic fertilizer (POC) to the growth and productivity of odot grass (Pennisetum purpureum cv. Mott).. The design used a non-factorial Group Random Design (RAK) with 4 treatments and 6 repeats. Treatment consists of: Po (without POC), P1 (POC Naturageen), P2 (D' Boostefer), and P3 (Pamorganic mas). The POC response to odot grass was carried out by applying a spray solution of 50 ml of liquid organic fertilizer (POC) then watering each plot and 4.5 liters of water for each treatment using POC. The parameters observed were the height of odot grass, number of tillers, leaf length, number of leaves, and production of segat odot grass. Observations were made from 2 WAP (week after planting) until 8 WAP. The data generated through measurements was analyzed statistically and tested with DMRT. From the results of the research analysis, it was found that the use of odot grass POC had a significant effect (p<0.05) on the growth and productivity of odot grass compared to the control (without POC), with the effectiveness or good effect being P2 > P3 > P1, while P0 was growth and the lowest production.